'MGUEDA'S ODE TO THE JET" OR THE TROUBLED APPROPRIATION OF MODERNITY - Mudarra Montoya, Américo (2009)
In the present article the poem "Ocle to the Jet" of }ose Maria Arguedas, is studied fromthe perspective of modernity. This poem constitutes a song to an element strange inthe Quechua world. The lyric speaker shows admiration befare an objecr of modernityseeking to wesrernize the Quechua culture.